KEEFEKTIFAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK LATIHAN ASERTIF UNTUK MENINGKATKAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK KELAS IX SMP NEGERI 5 PONTIANAK - Andini Putri; Muhammad Asrori; Halida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to test the effectiveness of group counseling services using assertiveness training techniques to improve students’ interpersonal communication at SMP Negeri 5 in Pontianak. This study employed an experimental method with a pre-experimental design, specifically a one-group pretest-posttest design. The data collection technique used was the Interpersonal Communication Inventory. Data analysis was conducted using the parametric Paired Sample T-Test. The results showed that students’ pretest scores had an average percentage of 44.25%, falling into the low category, while their posttest scores had an average percentage of 72%, falling into the high category, representing an increase of 27.75%. The results of the hypothesis test showed that the t-value was -12.511 with a significance level of 0.000 < 0.05, which means that H0 was rejected and Ha was accepted. Thus, it can be concluded that there was a significant improvement after group counseling using assertiveness training techniques to enhance the interpersonal communication skills of students at SMP Negeri 5 in Pontianak.